Link design for 5G communication system - Myo Bala Thann Swe (Nanyang Technological University, 2023)
Massive multiple input multiple output proposed wireless access method for 5G radio link design to meet the needs of wireless networks. The report includes research that promotes the development of applications that use massive MIMO technology and possibly used to revamp the spectral efficiency per cell of wireless networks by using a signal processing approach. Massive MIMO is especially researched utilizing mmWave frequencies and distributed antenna systems, both of which are being developed in academia and industry for future wireless networks. The first portion of the thesis provides a high-level explanation of the needs for future wireless networks as well as a discussion of some of the mathematical ideas employed in existing massive MIMO literature. The fundamental contrasts between massive MIMO approaches that use cellular frequencies and those that use mmWave are then given and thoroughly examined. Then, at mmWave frequencies, "doubly massive MIMO" systems, which employ a huge number of antennas at both the transmitter and the receiver, are created. Due to complexity and energy consumption difficulties, fully digital pre-coding and post-coding structures may be infeasible; hence, suboptimal alternatives, such as the use of fewer radio-frequency chains and reduced hardware, have been considered. Multiple signal processing functions including DCS-SOMP are examined and their relative performance is assessed utilizing a large number of antennas. Under some settings, low-complexity beam-steering totally analogue beamforming may be an acceptable performance-complexity trade-off solution, while simulated simulations imply that fully digital beam formers may achieve higher energy efficiency than lower-complexity systems. The dissertation then examines the newly developed cell-free massive MIMO architecture, in which plenty of scattered access points linked to a central processing unit concurrently and collaboratively service a significantly fewer of mobile bases. Instead of the previously planned cell-free massive MIMO, the research also takes angles of arrival as well as angle of departure with line of sight in which each mobile station is only supported by a small number of access points. It is also proposed that the positioning and orientation approach's uplink’s performance be enhanced by using spatial signal and phased array signal-processing methods. All of the suggested systems are capable of operating independently of the main computer, enabling decentralized implementation. The numerical results show that the massive MIMO approach outperforms for the vast majority of users in the system. The results show that the suggested signal processing algorithms outperform their counterparts by a substantial margin which in turn leads to estimate the theoretical transmission distance.